The Effect of Giving Banana Heart Nuggets on Breast Milk Production in Breastfeeding Mothers in Kelumpang Village in 2022 - Veronika, Desi; Wahyutri, Endah; Abdul Syukur, Nursari (Rifa'Institute, 2022)
Introduction: Mother's milk (ASI) is a very important food and drink for babies. In exclusive breastfeeding given for 6 months without any additional food. One of the efforts made to obtain children with good growth and development is to provide exclusive breastfeeding until the baby is 6 months old and continued until 24 months old baby. Objective: This researchers want to provide interventions to increase breast milk production in mothers breastfeeding Methods: This type of research is a quantitative study with a quasi-experimental research method (quasi- experimental) with a research design that is pre-test post-test non-equivalent control group. Observation sheet measuring instrument. Data analysis using paired t test and independent test. Results: There is no significant difference in the average of respondents' breast milk expenditure between the intervention group and the control group at the pretest p-value of 0.033 (p < 0.05) and there is a significant difference on the average respondent's milk expenditure between the intervention group and the control group at the posttest the p value was 0.000 (p < 0.05). Discussions: Banana heart contains calories, protein, fat, carbohydrates, vitamin A, vitamin B1, vitamin C and minerals such as phosphorus, calcium and Fe and stimulates the oxytocin and prolactin hormone which will greatly assist the process of breast milk production. Conclusion: Giving banana hear nugget has an effect on breast milk production